ENTREPRENEURSHIP AND INNOVATION: ANALYSIS OF INNOVATION RATES OF ENTERPRISES BASED ON THE BRAZILIAN RESEARCH DEVELOPED BY THE GEM 2006, 2007 AND 2008 - Fiorin, Márcia Meira Berti; Mello, Cristiane Marques de; Machado, Hilka Vier (Revista de Administração da UFSM, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->Entrepreneurship is understood as a process which makes something creative and innovative, aiming to generate wealth and value for individuals and for society (FILION, 2004; SHANE; VENKATARAMAN, 2000; BRUYAT; JULIEN, 2000. Entrepreneurship involves recognizing <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->the opportunity to create something new, but the recognition of an opportunity to develop a new market, using a new raw material or develop a new means of production (SCHUMPETER, 1982; BARON; SHANE, 2007). This study aims to describe and analyze aspects related to innovation of enterprises based on the Brazilian research developed by the GEM - Global Entrepreneurship Monitor. The data used for the development of the study are secondary data and were published in those reports for the years 2006, 2007 and 2008. The search results classify Brazil among the countries most entrepreneurs, however, such studies have shown that the country has low rates when it comes to innovation in business. Thus, the study includes some notes regarding the possible reasons leading to low rates of innovation in Brazilian companies.